1989
DOI: 10.1159/000125134
|View full text |Cite
|
Sign up to set email alerts
|

Role of Steroid 5α-Reductase Activity in Sexual Differentiation of the Guinea Pig

Abstract: The possible role of 5α-reduction of steroids in the sexual differentiation of guinea pigs was determined by treating pregnant guinea pigs with a 5α-reductase activity (5αRA) inhibitor (17β-N, N-diethylcarbamoyl-4-methyl-4-aza-5α-androstan-3-one, 4MA, 10 mg/day) from day 30 to 55 of gestation. 5αRA in fetal diencephalon tissue obtained from 4MA-treated mothers on day 55 of gestation was suppressed compared to that of control tissue. Four litters receiving 4MA were carried to term along with an equal number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
2
2
Order By: Relevance
“…These data imply that the cellular events that mediate the organization of positive and negative feedback control mechanisms of gonadotropin release have different hormonal components or dose requirements for estrogen during fetal life. The present results differ from those of similar experiments using a 5oa-reductase inhibitor [11]. In those experiments, fetal guinea pigs of both sexes exposed to a 5ot-reductase inhibitor in utero were capable of responding to the negative feedback action of estrogen on LH secretion in adulthood [11].…”
Section: Fea Mawcontrasting
confidence: 99%
See 2 more Smart Citations
“…These data imply that the cellular events that mediate the organization of positive and negative feedback control mechanisms of gonadotropin release have different hormonal components or dose requirements for estrogen during fetal life. The present results differ from those of similar experiments using a 5oa-reductase inhibitor [11]. In those experiments, fetal guinea pigs of both sexes exposed to a 5ot-reductase inhibitor in utero were capable of responding to the negative feedback action of estrogen on LH secretion in adulthood [11].…”
Section: Fea Mawcontrasting
confidence: 99%
“…The present results differ from those of similar experiments using a 5oa-reductase inhibitor [11]. In those experiments, fetal guinea pigs of both sexes exposed to a 5ot-reductase inhibitor in utero were capable of responding to the negative feedback action of estrogen on LH secretion in adulthood [11]. Gonadectomized males thus treated, however, possess lower LH levels in their sera than do untreated controls, indicating that the development of mechanisms that control the postcastration rise of gonadotropin is androgen-dependent.…”
Section: Fea Mawcontrasting
confidence: 99%
See 1 more Smart Citation
“…Alternatively, both sexes may respond to an E 2 challenge by releasing surge amounts of LH, as is the case in primates [8]. The effects of an E 2 challenge on LH in our AA-treated hyenas will also be of interest, because Connolly and Resko [43] found that female guinea pigs treated prenatally with a 5␣-reductase inhibitor showed a greater LH response to E 2 treatment. Given the profound organizational effects that prenatal androgens have on the hypothalamic-pituitary unit in a diverse group of female mammals, how the highly virilized female spotted hyena escapes those effects remains an open and intriguing question.…”
Section: Fig 7 Mean (ϯSem) Plasma a 4 (A) And T (B) Concentrations mentioning
confidence: 99%